2017
DOI: 10.3233/bmr-150429
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and pain processing in adults with chronic low back pain compared to pain-free controls

Abstract: Abstract. BACKGROUND: Pain sensitivity has been negatively associated with physical activity levels. Few studies have examined associations between experimentally induced pain sensitivity and physical activity in adults with chronic low back pain and painfree controls. OBJECTIVE: The objective of this study was to examine associations between physical activity levels and how an individual processes pain using experimentally induced pain stimuli. METHODS: Seventy subjects (CLBP = 49; mean age = 46.8 ± 14.9; Pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…However, if chronic pain is already present, this might, in some cases, sensitize individuals to pain in such a way as to act contrary to the benefits of PA on pain sensitivity. Indeed, the presence of chronic pain has been reported to coincide with a lacking, or even reversed, association between habitual PA and pain sensitivity (Mani et al., 2019; Orr et al., 2017), and identical acute exercise regimens can produce different central pain processing responses across different painful conditions (Meeus et al., 2015). It is therefore of interest to further assess how the presence of chronic pain might influence the relationship between levels of habitual PA and the experience of painful stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…However, if chronic pain is already present, this might, in some cases, sensitize individuals to pain in such a way as to act contrary to the benefits of PA on pain sensitivity. Indeed, the presence of chronic pain has been reported to coincide with a lacking, or even reversed, association between habitual PA and pain sensitivity (Mani et al., 2019; Orr et al., 2017), and identical acute exercise regimens can produce different central pain processing responses across different painful conditions (Meeus et al., 2015). It is therefore of interest to further assess how the presence of chronic pain might influence the relationship between levels of habitual PA and the experience of painful stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…using a vacuum cleaner) and sports and exercise (Public Health England, ; World Health Organization, ). Physical inactivity has been strongly associated with the development and exacerbation of chronic health problems, including diabetes mellitus, ischaemic heart disease, cancer (Lee et al, ) and musculoskeletal complaints such as neck pain (Hallman, Ekman, & Lyskov, ), low back pain (Orr, George, & Simon, ) and lower limb osteoarthritis (Stubbs, Hurley, & Smith, ). To date, no review has been published that synthesizes the possible association of physical (in)activity in the development of WRUQDs across multiple occupational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, a recent study demonstrated no relationships between moderate or vigorous PA levels and heat-evoked TS of pain in a group of individuals with low back pain. 59 Lack of null relationships between MTS and PA/SB measures in this study can be due to observations: lower and skewed MTS change score at the symptomatic site (mean [SD]: 1.9 [1.8]); skewed PA data; inter-regional TS differences (lower scores—neck/shoulder regions vs higher scores at low back/knee/hip regions); higher MTS-S scores in older adults group (vs <65 years); and higher MTS at the painful site (vs remote site). Besides, there is some evidence demonstrating hypoesthesia in the painful region and no signs of CS, 30,35 which may have influenced the TS responses in the symptomatic region.…”
Section: Discussionmentioning
confidence: 99%
“…23,33,34 Moreover, no associations were found between pain processing measures and PA levels in individuals with chronic low back pain, suggesting a potential confounding of relationship by psychosocial factors. 59 Therefore, it is essential to understand the PA relationships with various clinical markers of nociceptive processing and modulatory processes while taking into account a range of confounding factors such as pain catastrophizing and sleep quality. 5,6,33,34,74,76…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation